Nanotechnology Implementation as Root Canal Sealer - Tiffany, Sasha Allayya; Abidin, Trimurni; Prasetia, Widi (TALENTA, 2024)
The application of nanotechnology is becoming increasingly prevalent in the field of dentistry. Specifically, in root canal treatment, the expulsion of microbes remains a challenge often leading to failure of the procedure. The use of sealer is an effective method to dispose of microbes, but the structure of root canal which features dentinal tubules ranging from micro to nano size underscores the need for nanoparticle sealer. Therefore, this review aimed to evaluate the implementation of nanomaterials as root canal sealer. The results showed that nanoparticle sealer increased the apical sealing ability of root canal obturation material. The concept of using nanoparticles in endodontics as a new treatment efficacy against the hidden microbes in dentinal tubules appeared to be a promising approach. The development of nanotechnology could be used to improve the ability of sealer to penetrate dentinal tubules to achieve successful root canal treatment.